2003
DOI: 10.1128/jvi.77.19.10689-10694.2003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Subgenomic Hepatitis C Virus Replicon RNA Levels in Huh-7 Cells after Exposure to Nucleoside Antimetabolites

Abstract: Treatment with antimetabolites results in chemically induced low nucleoside triphosphate pools and cell cycle arrest in exponentially growing cells. Since steady-state levels of hepatitis C virus (HCV) replicon RNA were shown to be dependent on exponential growth of Huh-7 cells, the effects of antimetabolites for several nucleoside biosynthesis pathways on cell growth and HCV RNA levels were investigated. A specific anti-HCV replicon effect was defined as (i) minimal interference with the exponential cell grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 23 publications
7
64
0
Order By: Relevance
“…siRNAs targeting CAD (carbamoyl-phosphate synthetase 2, aspartate transcarbamylase, and dihydroorotase), a tripartite enzyme that catalyzes the first three steps of pyrimidine biosynthesis, inhibited both the Luc-1b replicon and JFH1-2a virus expression. This activity is consistent with the known inhibitor of this enzyme, leflunomide, which has been shown previously to inhibit both respiratory syncytial virus and HCV (12,54). siRNAs targeting the mevalonate (diphospho) decarboxylase (MVD) enzyme, which catalyzes the formation of mevalonate, were found to inhibit Luc-1b replication (19).…”
supporting
confidence: 61%
“…siRNAs targeting CAD (carbamoyl-phosphate synthetase 2, aspartate transcarbamylase, and dihydroorotase), a tripartite enzyme that catalyzes the first three steps of pyrimidine biosynthesis, inhibited both the Luc-1b replicon and JFH1-2a virus expression. This activity is consistent with the known inhibitor of this enzyme, leflunomide, which has been shown previously to inhibit both respiratory syncytial virus and HCV (12,54). siRNAs targeting the mevalonate (diphospho) decarboxylase (MVD) enzyme, which catalyzes the formation of mevalonate, were found to inhibit Luc-1b replication (19).…”
supporting
confidence: 61%
“…In this class, we especially noticed that methotrexate (an anticancer drug) showed very strong anti-HCV activity (EC 50 0.1 M; CC 50 >200 M; SI >2000) in the ORL8 assay (upper panel in Fig. 1A and Table 1), whereas methotrexate showed very weak anti-HCV activity (EC 50 >200 M; CC 50 >200 M) in the OR6 assay as well as in a previous report [13] (upper panel in Fig. 1A and Table 1).…”
Section: Evaluation Of 26 Reagents For Anti-hcv Activity Using Or6 Anmentioning
confidence: 92%
“…Although methotrexate showed very weak anti-HCV activity in the HuH-7-derived assay (Con-1 strain) used in a previous study [13] as well as in our OR6 and AH1R assays (O and AH1 strains), the ORL8 assay revealed very strong anti-HCV activity (SI >2000). Such drastic differences in both assays suggest that some host factor or factors required for HCV RNA replication are different between these two cell lines, although the anti-HCV target of methotrexate is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…If estimates of 1,000-5,000 copies of replicon per stable replicon cell are accurate (24), the starting pool of 10 5 replicon cells in this assay contained more than 10 8 replicons. We previously showed that mutations resistant to 150 nM HCV-796 were present at a relative frequency of 1.1%, and that same concentration produced more than 800 distinct resistant foci in this assay.…”
Section: Discussionmentioning
confidence: 99%